New Findings on Evolution of Metal Homeostasis Genes: Evidence from Comparative Genome Analysis of Bacteria and Archaea - Coombs, J. M. (American Society for Microbiology, 2005)
In order to examine the natural history of metal homeostasis genes in prokaryotes, open reading frames with homology to characterized P(IB)-type ATPases from the genomes of 188 bacteria and 22 archaea were investigated. Major findings were as follows. First, a high diversity in N-terminal metal binding motifs was observed. These motifs were distributed throughout bacterial and archaeal lineages, suggesting multiple loss and acquisition events. Second, the CopA locus separated into two distinct phylogenetic clusters, CopA1, which contained ATPases with documented Cu(I) influx activity, and CopA2, which contained both efflux and influx transporters and spanned the entire diversity of the bacterial domain, suggesting that CopA2 is the ancestral locus. Finally, phylogentic incongruences between 16S rRNA and P(IB)-type ATPase gene trees identified at least 14 instances of lateral gene transfer (LGT) that had occurred among diverse microbes. Results from bootstrapped supported nodes indicated that (i) a majority of the transfers occurred among proteobacteria, most likely due to the phylogenetic relatedness of these organisms, and (ii) gram-positive bacteria with low moles percent G+C were often involved in instances of LGT. These results, together with our earlier work on the occurrence of LGT in subsurface bacteria (J. M. Coombs and T. Barkay, Appl. Environ. Microbiol. 70:1698-1707, 2004), indicate that LGT has had a minor role in the evolution of P(IB)-type ATPases, unlike other genes that specify survival in metal-stressed environments. This study demonstrates how examination of a specific locus across microbial genomes can contribute to the understanding of phenotypes that are critical to the interactions of microbes with their environment.